Potensi Artificial Intelligece (AI) Dalam Pelayanan Dan Pengawasan Pajak Di Indonesia Ditinjau Dari UU ITE, PP PSTE Dan UU KUP - Amrullah, Ahmad Syarief; Cahyadini, Amelia; Safiranita, Tasya (Equality : Jurnal Hukum dan Keadilan, 2024)
The application of artificial intelligence (AI) in tax services and supervision in Indonesia has raised attention due to its potential to improve efficiency and effectiveness in the digitization of the tax system. Currently, many problems are found in the digitization of tax services and supervision in Indonesia, which include difficulties in detecting fraud, data manipulation, unresponsive services, and false financial reports, which should not occur. Therefore, the purpose of this research is to explore the potential of AI in overcoming these taxation challenges and improving the performance of the tax system to be more effective, efficient, and accountable by reviewing existing related regulations and also examining the usefulness of using AI in meeting the needs of tax digitalization in the future. The research method includes literature analysis and case studies related to the implementation of AI in the context of taxation in other countries. The results of the analysis show that AI has great potential to improve the efficiency of tax services, detect fraud more accurately, and increase transparency or accountability in tax supervision, and meet the needs of the times although there are still challenges that must be overcome together.